Webster’s New World English grammar handbook - Loberger, Gordon J. (Hungry Minds, 2001)
This handbook covers all the basics of standard English usage in a concise, step-by-step format including the special "General Observation" feature that provides grammar rules and tips at a glance. This comprehensive reference is the perfect desktop reference for the non-writing professionals and students alike